Sex Determination and the Human Person - Penner, Myron A.; Cordero, April M.; Nichols, Amanda J. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2023)
Abstract: For many species that reproduce sexually, how sex is expressed at different points across lifespan is highly contingent and dependent on various environmental factors. For example, in many species of fish, environmental cues can trigger a natural process of sex transition where a female transitions to male. For many species of turtle, incubation temperature influences the likelihood that turtle eggs will hatch males or females. What is the case for Homo sapiens? Is human sex expression influenced by contingent environmental factors like we see in fish and turtles, with whom we share common ancestry and DNA? Our paper explores the current biological science of sex determination and how it applies to philosophical and theological accounts of the human person. We argue that while human sex determination is not susceptible to environmental cues to the same degree we see in other species, there is sufficient variability among the pathways of human sex development to complicate simplistic biological categories of male and female.